2009
DOI: 10.1002/aqc.1065
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for management strategies of invasive crayfish populations with an emphasis on biological control

Abstract: 1. The white-clawed crayfish, Austropotamobius pallipes (Lereboullet), is the only freshwater crayfish indigenous to Great Britain and Ireland. It has a widespread, though declining distribution in England and parts of Wales but does not occur naturally in Scotland. 2. The North American signal crayfish, Pacifastacus leniusculus (Dana), is not native to Europe and was introduced to Britain in the 1970s. The signal crayfish out-competes the native white-clawed crayfish as it is larger and more aggressive. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 76 publications
0
69
0
Order By: Relevance
“…Biological control methods were also employed worldwide, including the use of fish predators, disease-causing organisms and microbes that produce toxins (Holdich et al, 1999;Frutiger and Müller, 2002) but the only method that has been successful so far is the use of predaceous fish like eels, burbots, perches and pikes (Westman, 1991;Aquiloni et al, 2010;Freeman et al, 2010). Nevertheless, biocontrol might be risky since it may lead to new species introductions and it is not specific to the target organism, possibly also affecting native organisms as well.…”
Section: Management and Controlmentioning
confidence: 99%
“…Biological control methods were also employed worldwide, including the use of fish predators, disease-causing organisms and microbes that produce toxins (Holdich et al, 1999;Frutiger and Müller, 2002) but the only method that has been successful so far is the use of predaceous fish like eels, burbots, perches and pikes (Westman, 1991;Aquiloni et al, 2010;Freeman et al, 2010). Nevertheless, biocontrol might be risky since it may lead to new species introductions and it is not specific to the target organism, possibly also affecting native organisms as well.…”
Section: Management and Controlmentioning
confidence: 99%
“…With the possible exception of electrofishing (which, however, is not feasible in deep or turbid waters, can remove a modest portion of a population, and is not efficient in streams with large stones or where crayfish hide in the banks; Westman et al 1978;Freeman et al 2010), mechanical removal is often biased by crayfish size and sex, as shown by several studies. Catches of both O. rusticus in the USA (Bills and Marking 1988) and P. leniusculus in the UK and in the Czech Republic (Kozak and Policar 2003) were dominated by adult males.…”
Section: Mechanical Removalmentioning
confidence: 99%
“…A glimpse to the ongoing research in the matter will be also given. With respect to other previous reviews (Holdich et al 1999;Peay 2009;Freeman et al 2010), this paper will discuss new methods and will extend the analysis to the entire suite of invasive crayfish species.…”
Section: Introductionmentioning
confidence: 99%
“…using chemicals, crayfish 'plague' against susceptible NICS, trapping and biological control by stocking crayfish predators) is dependent on the time of the initial detection of NICS, overall cost and the size of the water body. Accordingly, no simple method effectively eradicating NICS is currently available or is likely to be in the near future (Freeman et al, 2010;Gherardi et al, 2011). Therefore, indirect metabolic rifts are continuously created by the spread of NICS through direct impacts on ICS and other aquatic biota and structural modification of habitats (i.e.…”
Section: > Ecological Status and Nicsmentioning
confidence: 99%